Next-generation sequencing of adrenocortical carcinoma reveals new routes to targeted therapies. Issue 11 (30th July 2014) - Ross, J S; Wang, K; Rand, J V; Gay, L; Presta, M J; Sheehan, C E; Ali, S M; Elvin, J A; Labrecque, E; Hiemstra, C; Buell, J; Otto, G A; et al.
Abstract : Aims: Adrenocortical carcinoma (ACC) carries a poor prognosis and current systemic cytotoxic therapies result in only modest improvement in overall survival. In this retrospective study, we performed a comprehensive genomic profiling of 29 consecutive ACC samples to identify potential targets of therapy not currently searched for in routine clinical practice. Methods: DNA from 29 ACC was sequenced to high, uniform coverage (Illumina HiSeq) and analysed for genomic alterations (GAs). Results: At least one GA was found in 22 (76%) ACC (mean 2.6 alterations per ACC). The most frequent GAs were in TP53 (34%), NF1 (14%), CDKN2A (14%), MEN1 (14%), CTNNB1 (10%) and ATM (10%). APC, CCND2, CDK4, DAXX, DNMT3A, KDM5C, LRP1B, MSH2 and RB1 were each altered in two cases (7%) and EGFR, ERBB4, KRAS, MDM2, NRAS, PDGFRB, PIK3CA, PTEN and PTCH1 were each altered in a single case (3%). In 17 (59%) of ACC, at least one GA was associated with an available therapeutic or a mechanism-based clinical trial. Conclusions: Next-generation sequencing can discover targets of therapy for relapsed and metastatic ACC and shows promise to improve outcomes for this aggressive form of cancer.